Psicologia histórico-cultural e o desenvolvimento psiquico infantil : compreendendo o processo de escolarização - Silva, Valéria Garcia da (2010)
This work discusses about the process of scholarization and its importance to the infant psychical development according to the Historic-cultural Psychology. It is a bibliographic and empirical research. By bibliographic study it has been tried to comprehend the human development highlighting the infant period and the influence of the scholarization process on infant psychical development. By empirical research it has been aimed to verify how teachers of Elementary Schools in public education in a city of Paraná realize the learning process and human development and what they think about the scholarization influence (the scientific contents) on infant psychical development. The theoretical reference used in grounding and analyses of collected information was especially guided by Historic-cultural Psychology, which is based upon Historical and Dialectical Materialism of Karl Marx, which considers man in his relations of production and in a socio-historical context. The empirical research counted on the participation of fourteen public school teachers of elementary school in a city of Paraná. The collection of information was carried out through the semi-structured interview technique, based on a script consisting of eight items. The collected data were submitted to content analysis and structured in categories, which are presented on the tables. The results allowed a further clarification about the conceptions which guide the educator's work, indicating how they comprehend the role of scholarization in children's psychical development. Data show that most educators have their work based on a vision of biological development, whereby the child develops naturally and learning process is dependent on the biological maturation. In their answers, the teachers did not relate the processes of development and learning as interdependent. The outcomes also show that the teacher's value knowledge derived from everyday life, to the detriment of scientific content, which, according to the theory that underlies this research, is the engine of development. Nevertheless, we analyzed the information in view of current society, which promotes and emphasizes the importance of utilitarist knowledge, minimizes the importance of the teacher's role as a mediator of classic contents that promote the improvement of higher mental functions and provides the conditions for man think the reality in a more complex way. Therefore, we advocate an education that promotes humanization and psychical development of those who go through it and that value scientific knowledge and the role of the teacher.